New ways of creating and sharing bibliographic information: an experiment of using the Wikibase Data Model for UNIMARC data - Giovanni Bergamin; Cristian Bacchi (JLIS.it, 2018)
Starting from the consideration that UNIMARC (and in general the MARC) is in fact an ontology, this contribution proposes to make it explicit and to convert it – only at a syntactic level – in Linked Data / RDF structures through the use of the Wikibase data model. The outcome could therefore become not only the publication of data as LOD, but also an environment for the production of bibliographic data, that allows different ontological approaches. We illustrate the possibility to achieve a restructuring of the UNIMARC record into distinct items by data type (potentially referred also to the different FRBR entities), retaining the possibility to recover all the information of the original format. Then we highlight the Wikibase solutions that become exploitable for the MARC: “usable version” of the record, with explicitation of the encoded values, and definitions connected to the data in the same system; identification of univocal data with URIs, as required in the context of the semantic web; source of the data recorded for each field; statistics on the presence of fields and subfields; new storage format natively designed for collaborative editing; export of all elements in standard RDF; support of modification via open API.